Application of molecular tools in support of deployment of Theileria parva live vaccines - Bishop, Richard P.; Nene, Vishvanath M.; Spooner, P.R.; Mbogo, S.; Kariuki, D.; Payne, R.; Morzaria, S.P. (International Livestock Research Institute, 1999)
The primary goals of applying molecular tools, developed at ILRI in conjunction with the use of infection and treatment immunisation are quality control of vaccines; monitoring of possible vaccine breakthrough and breakdown; and assessment of the impact of introducing new parasite types on long-term efficacy of the vaccine. There are two main categories of tools available for use; serological such as schizont - specific monoclonal antibodies and DNA-based. This paper outlines serological techniques; and DNA-based techniques including southern blotting, polymerase chain reaction (PCR) and single strand conformation polymorphism (SSCP). It discusses quality control and markers for vaccine stocks; investigating possible vaccine breakdown and breakthrough; molecular epidemiology of ECF which deals with role of other theileria species, genetic variation between T. parva isolates and population genetics.